Empowerment of Postpartum Mothers through Belly Breathing Education and Lemongrass Aromatheraphy to Overcome Anxiety - Sri Subagio (Suluh Abdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service aims to improve the knowledge of postpartum mothers in Domas Pontang Village. Activities are carried out using the community development method through community empowerment, where postpartum women play a role as subjects and objects in health development. Evaluation was carried out using pre-test and post-test to measure the increase in knowledge of participants. The results showed an increase in knowledge, where the number of participants who understood the material well, sufficiently and poorly during the pre-test became good and sufficient in the post-test. In conclusion, education through community empowerment is effective in increasing the knowledge of postpartum women about belly breathing and lemongrass aromatheraphy to overcome anxiety in Domas Pontang Village.